2023
DOI: 10.1038/s41408-023-00886-8
|View full text |Cite
|
Sign up to set email alerts
|

Real-world experience of patients with multiple myeloma receiving ide-cel after a prior BCMA-targeted therapy

Abstract: Most patients with multiple myeloma experience disease relapse after treatment with a B-cell maturation antigen-targeted therapy (BCMA-TT), and data describing outcomes for patients treated with sequential BCMA-TT are limited. We analyzed clinical outcomes for patients infused with standard-of-care idecabtagene vicleucel, an anti-BCMA chimeric antigen receptor (CAR) T-cell therapy, at 11 US medical centers. A total of 50 patients with prior BCMA-TT exposure (38 antibody-drug conjugate, 7 bispecific, 5 CAR T) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 28 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…In two of the previous studies from this consortium, 13 it was shown that prior BCMA targeted therapy was associated with inferior depth and duration of response. One study also showed that with a shorter duration of exposure to the prior BCMA targeted therapy and a significantly longer time from the last BCMA targeted therapy exposure to leukapheresis as well as ide-cel infusion, patients seemed to achieve better outcomes with ide-cel as a sequential therapy.…”
Section: Discussionmentioning
confidence: 94%
“…In two of the previous studies from this consortium, 13 it was shown that prior BCMA targeted therapy was associated with inferior depth and duration of response. One study also showed that with a shorter duration of exposure to the prior BCMA targeted therapy and a significantly longer time from the last BCMA targeted therapy exposure to leukapheresis as well as ide-cel infusion, patients seemed to achieve better outcomes with ide-cel as a sequential therapy.…”
Section: Discussionmentioning
confidence: 94%
“…In our cohort, 8 patients received involved eld radiation therapy, resulting in one achieving VGPR, ve showing SD, and two experiencing PD. The median PFS was 6 months (range, [3][4][5][6][7][8][9][10][11][12][13]. However, due to the small number of patients undergoing this treatment, they were not included in the primary analysis for comparison with the remaining type of BT.…”
Section: Discussionmentioning
confidence: 99%
“…Limited by retrospective design and lacking BCMA data, reduced PFS might relate to decreased tumor BCMA expression [10]. Our previous data showed lower PFS post BCMA-targeted therapy [11], and hinted at compromised ide-cel efficacy within six months of such treatment [12].…”
mentioning
confidence: 92%